2020
DOI: 10.1111/mec.15346
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in paternal social status predict patterns of offspring growth and metabolic transcription

Abstract: One type of parental effect occurs when changes in parental phenotype or environment trigger changes to offspring phenotype. Such nongenetic parental effects can be precisely triggered in response to an environmental cue in time‐locked fashion, or in other cases, persist for multiple generations after the cue has been removed, suggesting multiple timescales of action. For parental effects to serve as reliable signals of current environmental conditions, they should be reversible, such that when cues change, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Age-dependent changes in sperm epigenome may be a part of normal developmental program shaped by natural selection to inform better fitness of offspring phenotypes. One recent study demonstrated that paternal dominance status determines the growth rate in offspring in mice, where offspring of dominant males grow faster than the offspring of subordinate fathers even if available food resources are the same ( Cauceglia et al , 2020 ). One interpretation of this intriguing finding is that in nature, dominance usually ensures better access to resources and may increase the fitness of faster-growing offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Age-dependent changes in sperm epigenome may be a part of normal developmental program shaped by natural selection to inform better fitness of offspring phenotypes. One recent study demonstrated that paternal dominance status determines the growth rate in offspring in mice, where offspring of dominant males grow faster than the offspring of subordinate fathers even if available food resources are the same ( Cauceglia et al , 2020 ). One interpretation of this intriguing finding is that in nature, dominance usually ensures better access to resources and may increase the fitness of faster-growing offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of enclosure, including additional photographs, and established/maintenance methods have been provided elsewhere in more detail (e.g. Cauceglia et al., 2020; Gaukler et al., 2015, 2016; Ruff et al., 2013, 2015). Within enclosures, populations are founded by 24–30 mice (16–20 females; 8–10 males); this asymmetric sex ratio is standard for this system and the increased number of females increases the opportunity for vertical transmission.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental populations of inbred mouse strains (Mus musculus domesticus) living in semi-natural enclosures provide the ideal opportunity for studying the causal impact of social environment on individual competitive and reproductive behaviours. Wild and laboratory mice establish and defend territories when given the space to do so, and territories allow males to monopolize or nearly monopolize access to food and mates [29][30][31][32][33][34][35][36][37]. And the identical genetics and standardized rearing conditions of inbred strains represent an extreme uniformity across individuals as compared with wild populations, allowing us to manipulate a single aspect of animals' social environments and draw causal conclusions about the impact of this manipulation [28].…”
Section: Introductionmentioning
confidence: 99%